Attitude scale toward traditional children’s motor games: a validity and reliability study - Eşkil, Remzi; Akbulut, Mehmet Kadir; Eşkil, Kezban Gülşen; Varol , Yaprak Kalemoğlu; Topateş, Tuba Kizilet (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
The aim of this study was to develop a scale that can validly and reliably measure students’ attitudes towards traditional children’s motor games. While developing the scale, an item pool was created, expert opinion was taken, a preliminary application was made and then validity and reliability studies were conducted. At first, an item pool was created with 31 students. Afterwards, a preliminary application was made on a group of 15 or 20 people. Exploratory Factor Analysis (EFA) was conducted with 795 participants, and Confirmatory Factor Analysis (CFA) was conducted with 392 participants. A valid and reliable measurement tool was developed based on the responses of a total of 1,187 participants. As a result of EFA, it was determined that the final scale consisted of 20 items and 2 sub-dimensions named as Positive Attitudes and Negative Attitudes, and this structure was confirmed by CFA. Cronbach’s alpha reliability coefficients were calculated as .95 for the Positive Attitudes sub-dimension, .91 for the Negative Attitudes sub-dimension and .95 for the whole scale. As a result, the findings show that the developed scale can measure students’ attitudes towards traditional children’s motor games in a valid and reliable way.